Relationship between BMD and Zn, Cu, Ca Levels in the Hair and Meal in Elderly People - 李万里 田玉慧 宋笑飞 张敏 沈关心 (Current medical science, 2005)
The relationship between bone mineral density (BMD) and Zn, Cu, Ca levels in the meal and hair of urban and rural elderly people were studied. 470 subjects above 60 years old (urban 205 and rural 265), 178 males with an average age of 68.70±3.48 and 292 females with an average age of 65.90±4.02, were inquired. The BMD and Zn, Cu, Ca levels in the meal and hair were measured. The detected BMD in urban and rural female old people was significantly lower than that of the males; The contents of Ca and Zn in the meal of the urban females were significantly lower than those of the urban males; The Ca, Zn in the meal and Zn in the hair of the rural females were significantly lower than those of rural males (P<0.05 or 0.01). The BMD, Ca intakes. Ca and Zn in the hair of the rural old people were significantly lower than those of the urban old people (P<0.05 or 0.01). There was a correlation between BMD with the Ca, Zn of the hair and dietary Ca,Zn, Cu or between dietary Zn with Ca, Zn in the hair and Ca, Cu intakes. The Zn, Cu and Ca levels in the meal nutrients were correlated with BMD.to some degrees. Lack of Ca and Zn in the meal can cause the reduction of BMD.